Cordycepin and N6-(2-Hydroxyethyl)-Adenosine from Cordyceps pruinosa and Their Interaction with Human Serum Albumin - Meng, Zebin; Kang, Jichuan; Wen, Tingchi; Lei, Bangxing; Hyde, Kevin David (PLOS ONE, 2015)
Cordyceps pruinosa (CP) is often used as Traditional Chinese Medicine, but the substance basis of its medicinal properties is unclear. In this study, two compounds were isolated from CP cultures by column chromatography, and identified as cordycepin and N6-(2-hydroxyethyl)-adenosine (HEA) by Nuclear Magnetic Resonance. In order to understand the efficacy of these two substances as potential therapeutic agents, it is necessary to explore their binding with proteins. The molecular mechanisms of interaction between cordycepin, HEA and human serum albumin (HSA) were studied using UV and fluorescence spectroscopy. The bingding constants between HSA and cordycepin were 4.227, 3.573 and 3.076 × 103·at 17, 27 and 37°C respectively, and that of HSA and HEA were 27.102, 19.409 and 13.002 × 103·at the three tempretures respectively. Both cordycepin and HEA can quench the intrinsic fluorescence of HSA via static quenching, and they can bind with HSA to form complexes with a single binding site. The interaction forces between cordycepin and HSA were determined as electrostatic and hydrophobic, and those of HEA and HSA were hydrogen bonding and van der Waals forces. Using Foster's equation, the distance between fluorophores of cordycepin and HSA, and HEA and HSA are estimated to be 5.31 nm and 4.98 nm, respectively. In this study, cordycepin was isolated for the first time from CP, and will provide a new source of cordycepin and expand the use of this taxon. The interaction mechanisms between cordycepin and HSA was studied for the first time, which will provide a useful guide for the clinical application of cordycepin. The pharmacological importance of this study is to understand the interaction of HSA with cordycepin and HEA, which will be essential for the future designing of drugs based on the two compounds.